The diagnostic value of H-index in S1 root compression. Issue 2 (February 1981) - Aiello, I; Rosati, G; Serra, G; Manca, M
Abstract : The H-index was studied in 42 healthy subjects and in 20 patients showing unilateral S1 root compression. When compared to the normal subjects, all patients showed a decreased H-index, or an increased difference in H-index between the sides or both. These results indicate that both parameters are valuable in the diagnosis of S1 root impairment due to intervertebral disc protrusion.